Influence Of Habits On Watching Movies And Abilities Creative Thinking About The Power Of The Short Story Language - Yumna Rasyid, Sukadir Kete, Aceng Rahmat (International Journal of Advanced Science and Technology, 2020)
This article is a development of a previous article about the ability to think creatively and its influence on the mastery of the language style of short stories. Mastery of language style is not only influenced by the ability to think creatively, but the habit of watching films also affects the mastery of language styles of short stories students. This study aims to analyze the effect of movie watching habits on mastery of short story language styles and the influence of creative thinking on mastery of short story language styles. The research method used is a quantitative approach and uses multiple regression analysis. The population of this research is all students of class XI IPA of SMA Neg. 5 Kendari. Furthermore, determining the sample using simple random sampling technique, so that a sample of 36 high school students was obtained. 5 Kendari Class XI IPA 1. Data collection techniques are carried out using tests and questionnaires. The results of the analysis of the research data show that there is a significant influence between the habit of watching films on mastery of the short story language style and there is a significant influence between creative thinking on the mastery of the short story language style. Great contribution to the influence of the habit of watching movies and creative thinking on mastery of language style that is equal to 59.60% and the rest is influenced by other factors outside this study.